Prevalence of HIV and Associated Risk Factors Among Infants Born to HIV Positive Mothers Attending Entebbe Regional Referral Hospital. - Wamala, Keefa; Nuwamanya , Ronald; Muwanga , Moses (Student's Journal of Health Research Africa, 2021)
Background: Uganda has an estimated 1.4 million people living with HIV with about 52,000 infections occurring every year. In 2018, 160,000 children were reported to have become infected with HIV. Globally, HIV exposed infants have delayed access to Early Infant Diagnosis (EID) of HIV, thus hampering efforts towards zero new infections. In Uganda, the prevalence of HIV among infants is not recorded, peak mortality for infants born with HIV occurs between 2 and 3 months of age. Vertical transmission of HIV from mother to child is the second commonest route of transmission of HIV in Uganda accounting for 18% of all new infections. This study assessed the prevalence of HIV and associated risk factors among infants born to HIV positive mothers attending Entebbe regional referral hospital. Methodology: a cross-sectional study was conducted at a paediatric ward and Mother-Child Health (MCH) General Department of Entebbe Regional Referral Hospital. The study included 78 HIV-exposed infants whose blood samples were collected and analyzed to know their HIV status and data about risk factors was also collected. Data were collected using questionnaires from mothers. Data were then entered into an Excel spreadsheet and analysed by SPSS Version 20. Results: The prevalence of HIV infection among HIV exposed infants is 5.1%. Delay in child diagnosis, breastfeeding was the factors that increased the risk of mother-to-child transmission of HIV in this study. Conclusion and recommendations: Having such a significant figure greater than the proposed WHO recommendation of less than 5% new infections in infants in the era of the world’s pledge to eliminate MTCT of HIV is unbearable therefore, interventions need to be done to lower this prevalence